Death and dying sociological perspectives - Cox, Gerry R.; Thompson, Neil, 1955- (New York, NY ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2020)
Death and Dying is an important core text for students and professionals interested in developing a holistic understanding of death and dying. Chapters are replete with case studies, activities, key point boxes, and other features that enable readers to develop a sociologically informed understanding of the broad range of complex issues that underpin death and dying. Written by two established and highly respected experts in the field, it offers a thoroughgoing account of a wide range of social aspects of death and dying, filling gaps left by the traditionally narrow focus of the existing literature. By drawing the suggested sociological perspectives and highlighting the role of social policy, the authors put forward a fresh perspective of the field of thanatology. This book is a major contribution in progressing knowledge and understanding of dying and death for students and professionals in counseling, healthand human services.
OCLC-licensed vendor bibliographic record.
Keywords: Death -- Social aspects; PSYCHOLOGY / Mental Health; SOCIAL SCIENCE / Sociology / General